2020
DOI: 10.7150/jca.35444
|View full text |Cite
|
Sign up to set email alerts
|

M2 Macrophages Promote HCC Cells Invasion and Migration via miR-149-5p/MMP9 Signaling

Abstract: The roles of M2 macrophages on promoting tumor progression and chemotherapy resistance have been well studied in many cancers, such as pancreatic cancer, kidney cancer and so on, but its linkage to HCC cells still remains unclear. Here we found that M2 macrophages could alter miR-149-5p to increase MMP9 expression in HCC cells and mechanism dissection revealed that miR-149-5p might directly target the 3'UTR of MMP9-mRNA to suppress its translation. The in vivo orthotopic xenografts mouse model with oemiR-149-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 27 publications
0
35
1
Order By: Relevance
“…MMP-9 is one key member of the MMPs family. The progression of various types of cancer, such as bladder, breast, esophageal squamous cell carcinoma, intrahepatic cholangiocarcinoma, hepatocellular carcinoma, is driven by the up-regulation of MMP-9 [ 135 , 136 , 137 , 138 , 139 ]. MMP-9 is able to cleave extracellular matrix components such as collagen or fibronectin, as well as many other non-collagenous substrates.…”
Section: Myc–a Key Player In the Tumor Microenvironment (Tme)mentioning
confidence: 99%
See 1 more Smart Citation
“…MMP-9 is one key member of the MMPs family. The progression of various types of cancer, such as bladder, breast, esophageal squamous cell carcinoma, intrahepatic cholangiocarcinoma, hepatocellular carcinoma, is driven by the up-regulation of MMP-9 [ 135 , 136 , 137 , 138 , 139 ]. MMP-9 is able to cleave extracellular matrix components such as collagen or fibronectin, as well as many other non-collagenous substrates.…”
Section: Myc–a Key Player In the Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…Furthermore, MMP-9 cleavage alters chemokines’ biological functions, and its activity can result in the shedding of cell surface receptors [ 140 , 141 ]. A recent study shows that alternatively-activated macrophages (M2) can increase the invasion and migration of hepatocellular carcinoma by up-regulating MMP-9 [ 139 ]. Additionally, Pello and colleagues revealed that MMP-9 is induced in TAMs upon MYC activation [ 24 , 30 ].…”
Section: Myc–a Key Player In the Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…Macrophages, a class of high plastic cells, can polarize into M1 or M2 subtypes in response to the surrounding microenvironment [6]. It's different from M1 macrophages, M2 macrophages play anti-inflammatory effects through producing anti-inflammatory cytokines such as interleukin (IL)-10 and transforming growth factor (TGF)-β, which is linked to immunosuppression and tumorigenesis [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, miR-942-5p, miR-29c-5p, and miR-551 were reported in other cancer types but not in HCC. For instance, high expression levels of miR-140-3p inhibit EMT, invasion, and metastasis of HCC by targeting GRN [ 24 ], whereas miR-9-5p and miR-149-5p promote HCC progression [ 25 , 26 ]. On the contrary, upregulation of miR-551a by dimethoxy curcumin hinders metastasis of ovarian cancer cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%